Aplikasi Android Untuk Mencari Jalur Tercepat Pada Pengiriman Barang Dengan Algoritma Held-Karp - Alfin H; Kartina Diah Kesuma Wardhani (Journal of Applied Informatics and Computing, 2020)
The total number of shipments to be sent from 2017 with an average total of 18 million shipments per month until 2018 reaches 24 million per month, while the process the shipping path is still as described and guessing, so couriers often wrong in estimating the fastest route or forgetting to order delivery based on previous couriers which cause the courier to have to turn around and every time the courier turns back then the shipping process becomes ineffective in terms of time, distance and cost. Based on the results of a 2018 study, Held-Karp produced a better route than Iterative Deepening Search in finding a shipping route. Therefore an Android-based application is created and uses the Google Maps API to determine the time, distance, and cost required at each point of delivery, as well as using the Held-Karp algorithm to search for the fastest path based on time, distance and cost. Based on functionality testing the application is estimated to run correctly and per the expected function, then in cyclometric complexity testing, the Held-karp algorithm is categorized in well-written and structured code and high testability because there is no v (G) above 10.